Effect of intelligence on consumers' responsiveness to a pro‐environmental tax: Evidence from large‐scale data on car acquisitions of male consumers. Issue 4 (14th March 2017) - Aspara, Jaakko; Luo, Xueming; Dhar, Ravi
Abstract: Researchers and policy‐makers are increasingly interested in the effects of pro‐environmental tax incentives on consumer responses. However, it is unknown whether consumers' responsiveness to pro‐environmental taxes depends on cognitive ability. We report a natural experiment study, in which a pro‐environmental tax was introduced in Finland, providing an economic benefit for cars with lower CO2 emissions. We examine 140, 000 car acquisitions by male consumers, whose intelligence had been tested by Finnish Defense Forces. The results show that the CO2 emissions of cars acquired by consumers with higher intelligence dropped more after the introduction of the tax than the emissions of cars of consumers with lower intelligence. Specifically, intelligence had both a direct effect on responsiveness to the pro‐environmental tax, and an indirect effect via income. The effect was more pronounced for numeric intelligence than verbal and spatial logic intelligence and of equal size as that of income and other demographics. This implies that intelligence is an empirically as well as theoretically relevant variable to study as a moderator to choices that are simultaneously pro‐environmental and economical.